New identities in Peru from media audiences - Cornejo Urbina, Franklin (2018)
This work deals with the social uses of the media in the Peruvian public context and proposes a theoretical and empirical approach about how music and soap operas serve to articulatesocial relationships and the formation of identities in collective cultural contexts.